Capital Structure and Financial Performance: Evidence from Listed Financial Sector Firms in ASEAN - Xasanov Diyorbek; Imas Nurani Islam; Nono Supriatna; Nuriddin Javliyev (Journal of Social Science and Humanities, 2026)
This study investigates the relationship between capital structure and financial performance among 1,483 listed firms in the TRBC Financials sector across Indonesia, Malaysia, and Singapore. Capital structure is measured using a composite leverage index, while financial performance is proxied by retained earnings scaled to total assets — a measure that captures cumulative rather than current-period profitability. Simple linear regression via SPSS yields no statistically significant association (R = 0.002; R² < 0.001; F = 0.005; p = 0.945; B = 0.002; β = 0.002). The adjusted R² is negative (−0.001), indicating that the model offers no predictive value beyond the unconditional mean of the dependent variable. Three factors account for this null result: heterogeneity of business models within the broad TRBC classification, the cumulative nature of the retained-earnings proxy, and the moderate leverage levels that prevail across ASEAN-listed financial firms. The findings align with the institutional contingency perspective and point toward multivariate panel designs as the appropriate empirical strategy for future research in this area.